The Influence of Painting on Enhancing Students’ Creative Thinking and Aesthetic Skills - Sohibova Zuhroxon Akmal qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the influence of painting on students’ creative thinking and aesthetic skills in higher education. It explores pedagogical approaches, interactive learning techniques, and the integration of modern technologies to improve students’ artistic expression, visual literacy, and problem-solving abilities. The study highlights the importance of both individual and collaborative painting activities in fostering holistic student development.